Implementasi Prinsip Kehati-hatian dalam Penyaluran Pembiayaan di Bank Syariah - Rizki, Ima Kurnia; Fatekhah, Putri Surya; Ali, Maslihan Mohammad (JIOSE: Journal of Indonesian Sharia Economics, 2024)
Islamic banking has the main function, namely as an institution that collects funds from the public in the form of deposits and distributes them back to the community in the form of financing (financial intermediary instution). The function of financing distribution carried out by Islamic banking to the public certainly has risks that require the implementation of prudential principles in these activities. The application of prudential principles carried out by Islamic banks is an obligation in order to protect public funds entrusted to Islamic banks. This research was conducted using descriptive qualitative methods to determine the implementation of prudential principles in financing analysis at Islamic banks. Data in this study was obtained through documentation from book sources, research journals and other related documents. The results of this study show that the application of the precautionary principle in financing analysis at Islamic banks can be carried out through the analysis of the 5C, 7P, 3R and 1S principles. This analysis is needed as a screening effort in the distribution of financing to the community.